Secondary Metabolites of Babandotan (Ageratum conyzoides L.) and Putri Malu (Mimosa pudica L.) to Control Fall Armyworm (Spodoptera frugiperda) - Dewi Anggraini; Wiwin Windriyanti; Sri Wiyatiningsih (The University of Lampung, 2025)
Corn (Zea mays) production in Indonesia has experienced fluctuations due to infestations of the fall armyworm (Spodoptera frugiperda). Utilizing botanical pesticides derived from Ageratum conyzoides (Babandotan) and Mimosa pudica (Putri Malu) is a method to control the fall armyworm and maintain stable corn production. This study aims to identify the active compounds and determine the effective concentration of A. conyzoides and M. pudica extracts in reducing S. frugiperda populations. The research was conducted from June to November 2024 at the Pest Laboratory of the UPT Plant Protection Unit in Surabaya. The study was designed using a Completely Randomized Design with a single factor: different concentrations of plant extracts, replicated five times. Observed parameters included phytochemical tests, GC-MS compound screening, larval symptoms, mortality rate, pupae formation, and imago formation. The results showed that A. conyzoides and M. pudica extracts at the highest concentration (1%) significantly affected mortality rates, pupation, and adult emergence. Both extracts contained flavonoids, tannins, and triterpenoids, which effectively controlled S. frugiperda populations. Keywords: Bioinsecticide, Spodoptera frugiperda, Zea mays.